Управління проектами в креативних індустріях у часи змін і викликів. - Павліха, Наталія; Pavlikha, Nataliia; Білоус, Олександр; Bilous, Oleksandr (Луцьк : Вежа-Друк, 2023)
The impact of creativity on the economy of sustainable community development is at a new stage of scientific research. This is primarily due to Russiaʼs full-scale invasion of Ukraine, the rapid pace of technology diffusion, geopolitical changes, the transformation of regional economies, the transition of modern society to sustainable, inclusive, and smart development, and the implementation of regional modernization strategies. At the same time, new forms of the spatial organization of the creative economy are being formed: the creative regions, creative clusters, creative spaces, and hubs. They are being developed on the basis of the experience of the European Union, the USA, Japan, and other developed countries.Вплив креативності на економіку сталого розвитку громад знаходиться на новому етапі наукових досліджень. Насамперед це пов’язано з повномасштабним вторгненням Росії в Україну, швидкими темпами поширення технологій, геополітичними змінами, трансформацією регіональних економік, переходом сучасного суспільства до сталого, інклюзивного та розумного розвитку та впровадженням стратегій регіональної модернізації. . Водночас формуються нові форми просторової організації креативної економіки: креативні регіони, креативні кластери, креативні простори, хаби. Вони розробляються на основі досвіду Європейського Союзу, США, Японії та інших розвинених країн.
Project management in the creative industries in times of change and challenges.
Keywords: creative industries; social development; project management; 502.333